The COVID-19's influence on customer purchasing behavior at foodpanda Bangladesh: New challenges and opportunities. - Mehzabin, Mubasshira (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2022.